Effect of long term-administration of aspartame on the ultrastructure of sciatic nerve. Issue 4 (December 2016) - Okasha, Ebtsam F.
Abstract: Aspartame is the most widely used artificial sweetener worldwide. There is much controversy about the effect of aspartame on different cells in the body. The aim of this study was to evaluate the effect of aspartame on the structure of the sciatic nerve. Thirty adult male albino rats were divided into three groups. Group I served as control; Group II received aspartame orally in a dose of 250 mg/kg/d for 3 months; Group III received aspartame at the same dose and for the same period, and was allowed to recover for 1 month. Specimens of sciatic nerve were processed, and semithin and ultrathin sections were examined by light and electron microscopy. A morphometric study was done to evaluate the g-ratio, which is the ratio between the axon diameter and total fiber diameter. Long-term aspartame administration resulted in many degenerative changes affecting mainly the myelin sheath, in the form of focal and extensive demyelination; disruption and splitting of myelin lamellae with loss of compact lamellar structure; and excessive enfolding with irregular thickening of myelin sheaths. Less frequent than those observed in the myelin sheath, some axonal changes were detected, such as compression and distortion. Dilated rough endoplasmic reticulum and vacuolation of the cytoplasm of Schwann cells were also detected. Partial improvement was observed in the recovery group. It was concluded that long-term administration of aspartame had a harmful effect on the structure of sciatic nerve and 1 month stoppage of aspartame was not enough to achieve complete recovery.